IMERSI DAN NOSTALGIA DALAM GAME A SPACE FOR THE UNBOUND - Pandu Rukmi Utomo; Krishna Hutama; Yan Yan Sunarya (Universitas Trisakti, 2022)
AbstractIs a research with goals to understand the relationship between immersion and nostalgia in Indonesian culture based game A Game For The Unbound. Research methodology used in this research is the aesthetic transformation method. This methodology is part of qualitative research in which the design object is reviewed by design critics and design discourse. The attention in details and understanding to the culture used trough aesthetic elements of video game is the most important factors to determine the success of A Game For The Unbound in creating immersion and nostalgia,Keywords: video game, culture, immersion, nostalgia AbstrakMerupakan sebuah penelitian yang bertujuan untuk menggali hubungan antara imersi dan nostalgia pada game Indonesia bermuatan budaya dengan judul A Game For The Unbound. Metode penelitian yang digunakan adalah transformasi estetik yang merupakan penelitian kualitatif dengan cara mengkaji sebuah objek desain melalui kritik desain dan wacana desain. Perhatian terhadap detail dan pemahaman terhadap budaya yang diangkat dalam elemen estetik video game merupakan faktor utama yang menentukan keberhasilan A Space For The Unbound dalam menciptakan imersi dan nostalgia.Kata kunci: video game, kebudayaan, imersi, nostalgia